Implementation of Areca flour (Areca catechu) as A Feed Additive On Precentage of Internal Organs of Broiler Chickens - Emy Saelan; Sri Lestari; Muhammad Ade Salim (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
The Research on Implementation of Areca flour (Areca catechu) as A Feed Additive on Precentage of Internal Organ of Broiler Chickens was carried out in the Poultry Production cage of the Animal Husbandry Study Program, Faculty of Agriculture, Khairun University in Fitu Village, South Ternate City. The research was carried out experimentally using a Completely Randomized Design (CRD) consisting of 6 treatments, namely R0 (100% commercial ration); R1 (99.5% commercial ration + 0.5% areca flour); R2 (99% commercial ration + 1.0% areca flour); R3 (98.5% commercial ration + 1.5% areca flour); R4 (98% commercial ration + 2% areca flour); and R5 (97.5% commercial ration + 2.5% areca nut flour) each treatment was repeated 4 times, so that 24 treatment units were obtained. Data obtained were analyzed with Analysis of Variance (ANOVA) one way and further tests with Duncan Multiple Range Test (DMRT). The variables observed include internal organs. The research results show that there was no significant difference (P>0.05) the internal organs of broiler chickens including liver, heart, and gizzard,  but there are significant differences (P<0,05) in the percentage of abdominal fat. The results of the study can be concluded that giving up to 2% areca flour (Areca catechu) the internal organs of broiler chickens